Data visualization and analysis within a Hydrologic Information System: Integrating with the R statistical computing environment - Horsburgh, Jeffery S.; Reeder, Stephanie L. (Environmental modelling & software : with environment data news, 2014)
This paper presents a prototype software system for visualization and analysis of hydrologic data that provides interoperability between the Consortium of Universities for the Advancement of Hydrologic Science, Inc. (CUAHSI) Hydrologic Information System (HIS) and the R statistical computing environment. By linking these two systems within a single desktop software application, an integrated hydrologic data management and analysis environment has been created that simplifies the process used by scientists and engineers to find, access, organize, and analyze the hydrologic data needed in modeling and managing hydrologic and environmental systems. The implementation of this work is a software plug-in for the CUAHSI HIS HydroDesktop software system called HydroR. We describe the design, graphical user interface, and implementation of the HydroR plug-in. An example application of HydroR is presented in which total suspended solids concentrations are modeled for the Little Bear River using a regression developed from turbidity and total suspended solids observations downloaded from the CUAHSI HIS using HydroDesktop. Finally, we conclude with a summary of our experience in developing interoperability between HIS and R and suggest future developments that can extend the capabilities we have developed. •We developed a software system that integrates the CUAHSI HIS and R.•HydroR combines data discovery and management with analysis and visualization in a single software environment.•HydroR reduces effort required to access data and transfer it into an analysis environment.•HydroR promotes repeatable analyses and may reduce potential errors.